2022
DOI: 10.1002/bse.3008
|View full text |Cite
|
Sign up to set email alerts
|

Strategic sustainable development of Industry 4.0 through the lens of social responsibility: The role of human resource practices

Abstract: Research on sustainable development is significantly influenced by the trade-off between the economic, social and environmental performance of businesses. Industry 4.0 development is a key business priority due to the promise of exponential increase in productivity, time efficiencies and cost reduction. However, Industry 4.0 development has been slow. Notably, human actors remain central to Industry 4.0, while the social responsibility component of sustainable development is a key prerogative for industry, cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(70 citation statements)
references
References 95 publications
0
53
0
2
Order By: Relevance
“…Digitization might support the information sharing intensity (Acerbi et al 2021), which represents an essential element in the context of sustainability (Jraisat et al 2021). Digitization also empowers the collaboration within a network among several actors, by also facilitating the knowledge sharing and commitment of human resources within the same factory, if human resource management practices are properly conducted (Mukhuty et al 2022). Actually, collaboration and exchange of information represent fundamental elements in embracing CM, especially if we look at the creation of industrial symbiosis networks (Martin and Harris 2018).…”
Section: Model Conceptualization: Literature Review Resultsmentioning
confidence: 99%
“…Digitization might support the information sharing intensity (Acerbi et al 2021), which represents an essential element in the context of sustainability (Jraisat et al 2021). Digitization also empowers the collaboration within a network among several actors, by also facilitating the knowledge sharing and commitment of human resources within the same factory, if human resource management practices are properly conducted (Mukhuty et al 2022). Actually, collaboration and exchange of information represent fundamental elements in embracing CM, especially if we look at the creation of industrial symbiosis networks (Martin and Harris 2018).…”
Section: Model Conceptualization: Literature Review Resultsmentioning
confidence: 99%
“…The Government of India has initiated efforts for smart advancements in manufacturing activities to instill a fast forward transition through the SAMARTH UDYOG BHARAT platform, to develop awareness through a consultative approach to accomplish objectives of I4.0 technology adoption in many industries by the year 2025 (Mukhuty et al, 2022 ). Thus, we believe based on the outcomes of this study, manufacturers will be motivated to adopt I4.0 technology enablers; as a result, the study may serve as a quick reference for consultants, service providers, and managers in strategizing and policy reforms to accelerate I4.0 adoption.…”
Section: Discussion and Study Implicationsmentioning
confidence: 99%
“…In this era of Big-Data, information is the new fuel for the economy (Stewart, 1998). Since information is a primary input to one's value chain operations for better performance (Danese et al, 2021;Mukhuty et al, 2022;Stewart, 1998), information generation, gathering, storage, and sharing are likely to play a critical role in value creation. In this paper, interactions among the agricultural value chain actors as critical stakeholders aimed at information sharing and value creation are referred to as the Sustainable Agricultural Value Chain (SAVC) partnership.…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, prior research considering the cross-functional multiparty relationship concerning information sharing and value creation has suggested that their interface exhibits many unclear characteristics (e.g., Niall & Rich, 2015;Porter & Millar, 1985;Prahalad and Ramaswamy, 2004;Xue et al, 2011). Fourthly, there is an undefined association between information sharing and value creation (Danese et al, 2021;Mukhuty et al, 2022;Porter & Millar, 1985). Therefore, the aim of this research is original in examining partnerships in the SAVC from a multidimensional perspective (Esfahbodi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%